2021
DOI: 10.1002/jgc4.1485
|View full text |Cite
|
Sign up to set email alerts
|

Contributors to and consequences of burnout among clinical genetic counselors in the United States

Abstract: Prior research has found that many genetic counselors (GCs) experience burnout.Studies of other clinicians have demonstrated that burnout can have significant detrimental consequences for clinicians, patients, and the healthcare system. We sought to explore the prevalence of, contributors to, and consequences of burnout among GCs. We performed a secondary data analysis of baseline data from Me-GC, a randomized controlled trial of meditation for GCs. We applied a systems model of burnout proposed by the Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Additionally, genetic counselors’ age, field experience, and/or comfortability in their professional role may impact their ability to benefit from mindful practices. Prior research indicates improved mindfulness has beneficial associations with burnout, compassion fatigue, work engagement, unconditional positive regard, and empathy among genetic counselors (Caleshu et al., 2021; Silver et al., 2018), suggesting genetic counseling students could also experience these benefits. These results demonstrate that there is a need for both increased self‐awareness and mindfulness levels in genetic counseling graduate students.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, genetic counselors’ age, field experience, and/or comfortability in their professional role may impact their ability to benefit from mindful practices. Prior research indicates improved mindfulness has beneficial associations with burnout, compassion fatigue, work engagement, unconditional positive regard, and empathy among genetic counselors (Caleshu et al., 2021; Silver et al., 2018), suggesting genetic counseling students could also experience these benefits. These results demonstrate that there is a need for both increased self‐awareness and mindfulness levels in genetic counseling graduate students.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication by Caleshu et al. (2021) reported a significant correlation between stress and burnout among practicing genetic counselors. Additionally concerning, genetic counselors with reported high anxiety were also at risk for compassion fatigue, a state of feeling overwhelmed resulting from an overuse of empathy (Lee et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Johnstone et al (2016) found that 40% of 353 surveyed genetic counselors considered leaving or did leave their jobs because of burnout. Other research describes how genetic counselors' interpersonal experiences can lead to burnout or compassion fatigue due to long-lasting emotional effects in the patient-counselor relationship (Caleshu et al, 2021;Lee et al, 2015;Udipi et al, 2008). Studies are needed to examine how the added layer of medical histories that parallel patient histories could affect genetic counselor burnout and compassion fatigue.…”
Section: Research Recommendationsmentioning
confidence: 99%